DIPLOMASI OLAHRAGA DALAM PERSPEKTIF KOMUNIKASI INTERNASIONAL MENYONGSONG ASIAN GAMES 2018 - Al Mansyur, Muh Isa (Transformasi, 2017)
This study aims to explain how the 2018 Asian Games can be an effective diplomacy strategy inIndonesia's international communications to the world community. International communicationin this research using diplomatic approach where the discussion concerning internationalrelations in communication science perspective. The study finds that the 2018 Asian Games apata Diplomacy Tool as a messaging symbol, a means of communication to improve or enhancereputation, other findings explain that sports can be a tool of symbolization in internationalcommunications to gain international recognition last Asian Games 2018 can be Aninternational communication tool to demonstrate attitudes toward behavior that are consideredopposed in the international system. Exercise can be a symbol in communication to convey aparticular message to the recipient, the effects of sports symbolization as an introduction to thiscommunication may vary. Similarly, the Asian Games 2018 which is an international sport eventcan be a strong symbol to improve diplomacy through international communication.Key word: Sports, International communication, symbols, communication, diplomacy.